2010
DOI: 10.1099/jmm.0.022491-0
|View full text |Cite
|
Sign up to set email alerts
|

Two Japanese Corynebacterium ulcerans isolates from the same hospital: ribotype, toxigenicity and serum antitoxin titre

Abstract: Two toxigenic Corynebacterium ulcerans isolates recovered from pharyngeal swabs of two patients from the same hospital in Japan during [2001][2002] were characterized by PFGE and ribotyping. Toxin production in different culture media was examined and serological analysis of patient sera was performed. The two isolates could not be distinguished by PFGE; however, their ribotypes were distinguishable. One of the isolates could represent a novel ribotype. Analysis of toxin production in different culture media d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Phylogenetic analysis of C. ulcerans isolates. C. ulcerans dog isolates obtained in this study (indicated in bold) as well as Japanese human isolates reported previously (Asakura et al, 2006;Hagiwara et al, 2006;Hatanaka et al, 2003;Komiya et al, 2010;Noguchi et al, 2009;Nureki et al, 2007) were analysed by PFGE as described in Methods. The phylogenetic tree was generated by the UPGMA method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis of C. ulcerans isolates. C. ulcerans dog isolates obtained in this study (indicated in bold) as well as Japanese human isolates reported previously (Asakura et al, 2006;Hagiwara et al, 2006;Hatanaka et al, 2003;Komiya et al, 2010;Noguchi et al, 2009;Nureki et al, 2007) were analysed by PFGE as described in Methods. The phylogenetic tree was generated by the UPGMA method.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, eight cases of infection by toxigenic C. ulcerans in humans were reported between 2001 and 2011 (Asakura et al, 2006;Hagiwara et al, 2006;Hatanaka et al, 2003Hatanaka et al, , 2011Komiya et al, 2010;Noguchi et al, 2009;Nureki et al, 2007;Yoshimura et al, 2010). C. ulcerans causes purulent inflammatory diseases such as mastitis, lymphadenitis, dermatitis and respiratory infections in various domestic and wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…Human C. ulcerans infections are caused by ingestion of untreated milk (Bostock et al, 1984) or close contact with animals (Hatanaka et al, 2003;Komiya et al, 2010;Tiwari et al, 2008). Our patient had six pet cats; although these animals were examined, C. ulcerans strains were not detected.…”
Section: Discussionmentioning
confidence: 70%
“…Because human infection with this bacterium has been frequently reported (Bonmarin et al, 2009;Katsukawa et al, 2012), the incidence of subcutaneous lesions due to C. ulcerans may increase in the near future. Therefore, the fact that C. ulcerans can cause a subcutaneous painful mass in the extremities is important for differential diagnosis.Human C. ulcerans infections are caused by ingestion of untreated milk (Bostock et al, 1984) or close contact with animals (Hatanaka et al, 2003;Komiya et al, 2010;Tiwari et al, 2008). Our patient had six pet cats; although these animals were examined, C. ulcerans strains were not detected.…”
mentioning
confidence: 70%
See 1 more Smart Citation